Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Panasonic - listiani, indah; Kamil, Musthafa (Jurnal Bintang Manajemen, 2024)
This study aims to determine the effect of compensation and work discipline variables on the performance of employees in the head office of PT. Panasonic, both partially and simultaneously. The method used in this study is a quantitative approach with associative research. The research sample consists of 53 people, selected using the Slovin formula from the total population. This study uses a simple random sampling method, with data collection techniques using a Likert scale questionnaire. Data analysis is conducted using data quality analysis, classical assumptions, and hypothesis testing, processed with IBM SPSS software version 27. The results of the study show that, partially, compensation has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, and simultaneously, both compensation and work discipline have a positive and significant effect on employee performance.